Research on gender differences of preparative motion for takeoff in the long jump - Murakami, Y.; Takahashi, K. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purposes of this study were to compare the preparative motion between female and male long-jumpers whose records were approximately the same, and to obtain the characteristics of motion of female long-jumpers. The motion was the female athletes have a larger extension angles and angular velocities of the hip and knee joint in the preparative phase than the male athletes. This motion influences on a CG drop which is the most important role for the preparation for takeoff. Upper body motion of female athletes indicated a large tilting range of motion at the time of each foot touching down. In addition, these two motions led the deceleration of the approach velocity. Therefore, it is thought that to improve these two motions resulting in better results.